Heat Transfer Fundamentals, Enhancement and Applications - Newaz Kazi, Salim (IntechOpen, 2023)
This book introduces the fundamentals, enhancements, applications, and modeling of heat transfer phenomena. Topics covered include heat transfer equations and applications in the estimation of heat energy transportation, heat transfer in specific applications, microchannel flow, condensation of refrigerants in modified heat exchanger tubes, alteration of tube surface texture for augmentation of heat transfer, boiling, etc. Also considered are fouling mitigation approaches to prolong heat exchanger operation, as well as tube coatings, heat exchanger digital twins, and various surface alteration techniques. Double-pass solar air heating and phenomena including heat transfer through thin liquid film and surface texture alteration for boiling heat transfer are discussed.